A multi-omic analysis of orange-spotted grouper larvae infected with nervous necrosis virus identifies increased adhesion molecules and collagen synthesis in the persistent state. Issue 98 (March 2020) - Ge, Hui; Lin, Kebing; Zhou, Chen; Lin, Qi; Zhang, Ziping; Wu, Jianshao; Zheng, Leyun; Yang, Qiuhua; Wu, Shuiqing; Chen, Wei; Wang, Yilei
Abstract: Grouper ( Epinephelus coioides ) is an important commercial maricultural fish, which suffers from nervous necrosis virus (NNV) infection. The molecular mechanisms underlying the pathogenesis of the viral infection are not clear. In this study, we combined deep RNA sequencing and label-free mass spectrum for the first time to analyze the transcriptomic and proteomic profiles in infected/dead, infected/survival (persistent), and infection-free (control)orange-spotted groupers in the larval stage. Further analyses showed that the transcriptome and proteome changed dramatically among the three distinct groups, especially differentially-expressed genes in the infected/dead and infected/survival larvae enriched for pathways related to immune response. Notably, the overlapped genes between transcriptomes and proteomes identified that genes related to collagen synthesis and adhesion molecules were enhanced in the persistent (infected/survival) stage, which might contribute to suppressing the acute and lethal immune responses upon NNV infection. These transcriptomic and proteomic datasets enable the investigation of molecular mechanisms underlying NNV infection, thus may help further development of molecular breeding in marine fishery. Highlights: We performed coalition analysis of transcriptomes and proteomes of NNV-infected grouper larvae. Differentially-expressed genes in the infected/dead and infected/survival larvae enriched for immune response pathways. The overlapped genes were related to collagen synthesis and adhesion molecules in the infected/survival larvae.